Live Loads for Rural Bridges - Shrestha, Jagat Kumar (Journal of the Institute of Engineering, 2009)
We find various loading standards for bridges in different countries based on their own contexts. In the context of Nepal, the road bridges have been designed adopting the various codes. Many of the bridges have been designed based on IRC and AASHTO standards. Nepal Road Standard (NRS 2027), has adopted the IRC and AASHTO loadings. The NRS covers loadings for the highway and feeder roads. The standard does not cover the loading standards for rural roads in Nepal. Now we have more than 20,000 km rural roads. This paper tries to review the live load standards which are being adopted in design of bridges in Nepal and recommend the live loads suitable for the bridges in rural roads specifically for district roads and village roads. For rural bridges, individual truck loading may be relevant rather than the train of loading. The 24R IRC loading may be an appropriate loading for rural bridges in Nepal. This represents a heavy vehicle plying in rural roads in Nepal. Key words: Live loads; Pem fuel cell; Self-organising maps; Journal of the Institute of Engineering, Vol. 7, No. 1, July, 2009 pp. 111-115 doi: 10.3126/jie.v7i1.2068